Hepatic interleukin‐1 receptor type 1 signalling regulates insulin sensitivity in the early phases of nonalcoholic fatty liver disease. Issue 9 (13th September 2022) - Gehrke, Nadine; Hofmann, Lea J.; Straub, Beate K.; Rühle, Frank; Waisman, Ari; Galle, Peter R.; Schattenberg, Jörn M.
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is associated with hepatic as well as systemic insulin resistance even in the absence of type 2 diabetes. The extent and pathways through which hepatic inflammation modulates insulin sensitivity in NAFLD are only partially understood. We explored the contribution of hepatic interleukin (IL)‐1 signalling in a novel conditional knockout mouse model and expand the knowledge on this signalling pathway with regard to its liver‐specific functions. Methods: A high‐fat, high‐carbohydrate diet (HFD) over 12 weeks was used in male hepatocyte‐specific IL‐1 receptor type 1 (IL‐1R1) knockout mice ( Il1r1 Hep−/– ) and wild‐type (WT) littermates. Results: Both genotypes developed an obese phenotype and accompanying macrovesicular hepatic steatosis. In contrast to WT mice, microvesicular steatosis and ballooning injury was less pronounced in HFD‐fed Il1r1 Hep−/– mice, and alanine aminotransferase remained in the normal range. This was paralleled by the suppression of injurious and proinflammatory hepatic c‐Jun N‐terminal kinases and extracellular signal‐regulated kinases signalling, stable peroxisome proliferator activated receptor gamma coactivator‐1alpha and farnesoid X receptor‐alpha expression and preservation of mitochondrial function. Strikingly, despite HFD‐feeding Il1r1 Hep−/– mice remained highly insulin sensitive as indicated by lower insulin levels, homeostatic model assessment for insulin resistance, higher glucose tolerance, more stable hepatic insulin signalling cascade, and less adipose tissue inflammation compared to the WT. Conclusions: The current data highlights that hepatocyte IL‐1R1 contributes to hepatic and extrahepatic insulin resistance. Future liver‐directed therapies in NAFLD could have effects on insulin sensitivity when improving hepatic inflammation and IL‐1R1 signalling. Abstract : Hepatic innate immune receptor controls whole body insulin sensitivity Intrahepatic and extrahepatic inflammation in a murine model of NAFLD is dampened following deletion of IL‐1R1 in hepatocytes IL‐1R1 controls lipid metabolism in the liver